Direct electrochemical extraction of metallic Li from a molecular liquid–Based electrolyte under ambient conditions. (10th February 2023) - Zhang, Haoyu; Zhang, Baoguo; Ai, Bing; Pan, Kefeng; Zhang, Weimin; Zhang, Lipeng; Shi, Zhongning
Highlights: Direct electrodeposition of Li from a molecular liquid–based electrolyte is achieved. A solution of LiCl in dimethylacetamide is used as the electrolyte. Li is deposited as LiAl master alloy produced via solid-state cathode alloying. Strategy for thin film-to-bulk conversion of electrodeposited materials is proposed. Guidance for continuous electrodeposition of bulk active metals is provided. Abstract: The high chemical activity of metallic Li hinders its efficient electrochemical extraction at low temperatures, necessitating the use of energy- and cost-intensive methods such as vacuum thermal reduction or electrodeposition from ionic-liquid and molten-salt electrolytes. Herein, we report the direct room-temperature electrowinning of metallic Li from a simple low-cost electrolyte, namely a solution of LiCl in dimethylacetamide (DMAc), determine the optimal concentration of LiCl, and examine the redox processes in the optimized system. Potentiostatic deposition on high-purity Al is shown to induce solid-state cathode alloying and thus produce a uniform, flat, and dense coating of a LiAl master alloy comprising spherical clusters formed by LiAl alloy nanosheets. Finally, the direct smelting of electrodeposited films is proposed as a method of rapidly realizing the "thin film" to "bulk" transformation of electrodeposited materials to stabilize metallic Li and form bulk Li-based alloys. Thus, this study provides a basis for the continuous, low-cost, sustainable, and fast electrochemical production of bulk active metals or their alloys.